7x + 10 = -7x - 60
Add 7x to both sides: 14x + 10 = -60
Subtract 10 from both sides: 14x = -70
Divide both sides by 14: x = -5
Chat with our AI personalities
7x + 5y 7(3) + 5(2) 21 + 10 = 31
7x+y=6
-7x - 2y = -3
7X + 2Y = 10 - 7X + Y = - 16 -----------------------just add 3Y = - 6 Y = - 2 --------------find X, top equation 7X + 2(- 2) = 10 7X - 4 = 10 7X = 14 X = 2 ------------check both original equations for consistency; top first 7(2) + 2(- 2) = 10 14 - 4 = 10 10 = 10 ------------top checks; now check bottom equation - 7(2) - 2 = - 16 -14 - 2 = - 16 - 16 = - 16 ------------------both check and are then consistent
7x + 2 = 6x + 2 if and only x = 0.